Knocking out or pharmaceutical inhibition of fatty acid binding protein 4 (FABP4) alleviates osteoarthritis induced by high-fat diet in mice. Issue 6 (June 2018) - Zhang, C.; Chiu, K.Y.; Chan, B.P.M.; Li, T.; Wen, C.; Xu, A.; Yan, C.H.
Summary: Objectives: Adipokines play roles in the pathogenesis of osteoarthritis (OA). Fatty acid binding protein 4 (FABP4) is a novel adipokine that is closely associated with obesity and metabolic diseases. The aim of this study was to discover the potential role of FABP4 in OA. Methods: Seventy-two FABP4 knockout mice (KO) in C57BL/6N background and wild-type littermates (WT) (male, 6-week-old) were fed with a high-fat diet (HFD, 60% calorie) or standard diet (STD, 11.6% calorie) for 3 months, 6 months and 9 months ( n = 6 each). In the parallel study, forty-eight 6-week-old male WT mice were fed with HFD or STD, and simultaneously treated with daily oral gavage of selective FABP4 inhibitor BMS309403 (15 mg/kg/d) or vehicle for 4 months and 6 months ( n = 6 each). Serum FABP4 and cartilage oligomeric matrix protein (COMP) concentration was quantified. Histological assessment of knee OA and micro-CT analysis of subchondral bone were performed. Results: HFD induced obesity in mice. After 3 months and 6 months of HFD, KO mice showed alleviated cartilage degradation and synovitis, with significantly lower COMP, modified Mankin OA score, and MMP-13/ADAMTS4 expression. After 6 months and 9 months of HFD, KO mice showed less osteophyte formation and subchondral bone sclerosis. Chronic treatment of BMS309403 for 4 months and 6 months significantly alleviated cartilage degradation, but had no effects on the subchondral bone. Knocking out or pharmaceutical inhibition of FABP4 did not have significant effects on lean mice fed with STD. Conclusions: Knocking out or pharmaceutical inhibition of FABP4 alleviates OA induced by HFD in mice.